Dance as a means of preventing diseases of civilization - Banio, Adrianna (Journal of Education, Health and Sport, 2018)
The aim of this study was to determine whether under the influence of dance classes favourable changes in the lives of people affected by diseases of civilization occur. The study group consisted of 56 middle-aged people, leading passive lifestyle (until they undertook activity in the form of dance). There were individuals having such health issues as: diabetes, coronary heart disease, cancer, problems with the spine as well as those being overweight and obese or living under high stress among them. The results show that dance activities cause many beneficial physiological changes in the body. They may reduce the risk of developing many diseases, which almost everyone is exposed to nowadays. Many also points out that the inclusion of dance exercises greatly improves their therapy’s efficiency.